2020
DOI: 10.1002/ett.4148
|View full text |Cite
|
Sign up to set email alerts
|

Permissionless proof‐of‐reputation‐X: A hybrid reputation‐based consensus algorithm for permissionless blockchains

Abstract: Over the past years, blockchain technology has become more and more interesting since its ability to carry out transactions without any mediator. To ensure the transactions' reliability, consensus algorithms are adopted by blockchain technology. However, due to the failure of consensus algorithms in managing nodes' identities, blockchain technology is considered inappropriate for many applications. In this article, we propose the permissionless proof‐of‐reputation‐X (PL‐PoRX) that upgrades an existing consensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 78 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Again, the Algorand blockchain assumes that there are 2 3 honest users/cryptocurrency-units selected in each step of the consensus round, including block proposal and validation. Hence, while proposing the block in step (r, 1), the probability of a malicious proposer getting selected as the highest priority proposer is 1 3 . One way in which a malicious proposer can harm the blockchain is by proposing a block consisting of transactions associated with malicious activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the Algorand blockchain assumes that there are 2 3 honest users/cryptocurrency-units selected in each step of the consensus round, including block proposal and validation. Hence, while proposing the block in step (r, 1), the probability of a malicious proposer getting selected as the highest priority proposer is 1 3 . One way in which a malicious proposer can harm the blockchain is by proposing a block consisting of transactions associated with malicious activities.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several methodologies integrate the user reputation in the blockchain consensus process with an aim to prevent illicit activities in blockchains. In [1], the authors proposed a permissionless proof of reputation consensus process. The entry for a user aspiring to join is based on a referral by an existing miner.…”
Section: Decentralised Reputation and Trust Modelsmentioning
confidence: 99%
“…As part of the consensus of the blockchain system, all the participating nodes must agree on the appended block, so another problem that the system needs to address is when the system splits into multiple nodes with different responses in the verification process. The authors of [ 36 , 37 , 38 ] introduce trust-based consensus protocols with a reputation scoring system; these papers suggest a rating system for the nodes in the network based on their participation in the consensus. An alternate way to calculate a node’s trustworthiness is using the Markov model [ 39 ].…”
Section: Background and Literature Studymentioning
confidence: 99%
“…Whereas the PoS consider the only the amount of stake in electing the node for block creation and validation 31 . Apart from the conventional consensus mechanisms some research works such as Reference 32 have shown interest to present reputation‐based consensus mechanism for permissionless blockchain. Authors in Reference 33 have present a novel proof‐of‐activity consensus mechanism by integrating the conventional PoW and PoW consensus mechanism for refining certain parameters including cost but the inherent nature of PoW prevents it from energy efficiency improvement.…”
Section: Literature Surveymentioning
confidence: 99%